TINJAUAN DATA WAREHOUSE DALAM ANALISA KECELAKAAN KERETA API (STUDI KASUS DI PT. KAI DAOP IV SEMARANG) - Wiwik Budiawan; Ary Arvianto Arvianto (Agroindustrial Technology, University of Trunojoyo Madura, 2014)
Data Warehouse is one of the important factors in providing data for decision-making process. One of them, the data and information used in the analysis of transport accident risk. PT. Kereta Api Indonesia (KAI) as a mode of transportation companies train operator, of course there are a variety of administrative and operational constraints in providing services to passengers. These constraints can impact on the schedule is delayed until the worst effects are accidents. When the train accident occurred, an investigation carried out on units allegedly linked to the contribution of the accident. However, the current investigation has not been able to run effectively and efficiently. This is because, the data and information some still manually (not computerized) and has not been arranged in the form of a data warehouse. This study is an initial step in the development of a train accident analysis system integrated. The output of this initial stage designed a data warehouse that is capable of providing data periodically and incidental to the process of decision-making, especially in the analysis of the accident. The method used to design a data warehouse is the Entity Relationship Diagram (ERD) and use MS SQL Server 2008 R2 software.